(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This literature review explores the complex interactions between the immune system, oxidative stress, and antioxidant defense mechanisms under various stress conditions. The study emphasizes that stress triggers a cascade of biochemical and physiological responses, leading to increased production of reactive oxygen species (ROS) and enhanced lipid peroxidation. These oxidative processes alter membrane integrity, enzyme activity, and immune cell function. The immune response under stress is characterized by changes in cytokine profiles, decreased lymphocyte activity, and dysregulation of humoral and cellular immunity. The review also highlights the compensatory role of antioxidant systems—such as superoxide dismutase, catalase, and glutathione peroxidase—in maintaining redox homeostasis. A balance between oxidative and antioxidant mechanisms is crucial for preventing tissue damage and maintaining immune competence. Understanding the interplay between immunological reactivity and oxidative stress provides new perspectives for developing therapeutic and preventive strategies aimed at enhancing the body’s adaptation to stress-related pathologies.